Power Allocation and Equivalent Transmit FDA Beamspace for 5G mmWave NOMA Networks: Meta-Heuristic Optimization Approach - Nusenu, Shaddrack Yaw; Huaizong, Shao; Ye, Pan (IEEE transactions on vehicular technology, 2022)
Most of the existing works in millimeter wave (mmWave) and non-orthogonal multiple access (NOMA) communications (mmWave NOMA) employs phased array (PA) antennas which yield only angle beamspace without range dependent, range-interference suppression and "dot-shaped" array resolution. In this paper, we propose a collocated transmitter (Tx) - receiver (Rx) mmWave NOMA system where frequency diverse array (FDA) antennas are utilized. FDA employs small frequency increments across the element indices which yields angle-range dependent beamspace. Herein, an equivalent radiate beamspace is designed to serve the users. Further, to ensure user equity, we formulate objective function to max-min achievable sum rate subject to power allocation and BS equivalent FDA transmit beamspace along the users. Since the problem is not convex, a boundary-compressed Bat meta-heuristic optimization algorithm is devised to provide a sub-optimal solution by optimizing the frequency increments to synthesis the BS beamspace along the users. The achievable secrecy rate, cost efficiency (CE), economic efficiency (ECE), and secrecy energy efficiency (SEE) are derived for the users. Both theoretical analysis and simulation results indicate that the proposed scheme would constitute an excellent nominee for 5G mmWave NOMA communication applications.